Kode Etik Guru dan Sikap Propesional Keguruan Indonesia - Rani, Indri Mustika; Rezeki, Ayu Sri; Nazla, Nazla; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The teacher's code of ethics is the basis of the behavior of Indonesian educators in carrying out their professional responsibilities in the field of education. The main purpose of formulating a code of ethics is to ensure that the work of a profession runs as expected and to protect the needs of all parties as it should. The purpose of this research is to find out whether or not the teacher's code of ethics has an influence on learning activities in schools. The research was carried out in an elementary school, with Islamic characteristics and based on nature. The research method used is a quantitative approach, using a sample of 10-25% of the population. The sample in this study is subject teachers, namely Islamic Religious Education, Sports and Health Physical Education, English teachers and Arabic teachers. This research was carried out up to four meetings, paying attention to the planning, implementation, evaluation and dissemination stages.  From the above definitions, it can be concluded that a professional teacher is a teacher who is able to carry out the educational process with high ability. Where, they master knowledge, are active in professional organizations, and understand the learning process completely. Alam examines the professional attitude of teachers in the perspective of Islamic education, 4 basic questions have been developed, namely: (1) what is the meaning of teachers' professional attitudes; (2) what is the target of the teacher's professional attitude; (3) how to develop a teacher's professional attitude; and (4) what is the professional attitude of teachers from the perspective of Islamic education? To answer these problems, the author studies them through literature searches, both based on theories and trade provisions, and through the study of the Qur'an and the Prophet's Hadith. The results of the literature search found that: (1) the teacher's professional attitude is an action or activity in the form of a good example in carrying out duties as a teacher who has high knowledge, attitude, and skills in carrying out the teacher's main duties; (2) the teacher's professional attitude includes: (a) attitude towards students; (b) attitude towards leaders/leaders; (c) attitudes towards colleagues; (d) attitude towards professional organizations; (e) attitude towards work; (f) attitudes towards the workplace; and (g) attitudes towards legislation; (3) the development of professional attitudes can be carried out through two stages, namely: pre-service education and in-service education/training; and (4) the attitude of professionalism in Islamic education, which is the action of a teacher who not only teaches but also educates with scientific and academic qualifications, but more importantly has commendable morals, such as having patience in teaching, conveying what is called for with honesty, and carrying out educational activities sincerely. It is hoped that this article can provide benefits and insights for readers regarding the professional attitude of teachers in the Islamic perspective and make it a basis for thinking and acting in carrying out the duties of the teaching profession, so that it is not only a devotee of duties and obligations, but at the same time as worship by Allah SWT.